Carbon encapsulated NiCo2S4 nanoparticles with enhanced surface mediated charge storage for superior ultracapacitor electrodes - Chaturvedi, Vikash; Pawar, Meenakshi; Thripuranthaka, M.; Shivade, Rajkiran; Shelke, Manjusha V. V. (Chemistry-An Asian Journal, 2023)
Three different compositions of NiCo2S4 (NCS) materials were prepared using three solvents, named NCS HTDI (hydrothermal in DI water), NCS STEG (solvothermal in ethylene glycol), and a novel carbon-encapsulated NCS STFA (solvothermal in formamide). The structural and morphological properties of the prepared NCS HTDI, NCS STEG, and NCS HTDI materials were analyzed using various physical characterization techniques. As prepared, NCS materials were tested as an electrode for supercapacitor (SC) application using a 3-electrode system in a basic electrolyte (3 M KOH). NCS HTDI exhibits a specific capacitance of 2536 F g(-1), NCS STEG shows 1355 F g(-1), and NCS STFA shows 1178 F g(-1) at an input current density of 1 A g(-1). The SBN-PSC material is utilized as a counter electrode in the NCS STFA || SBN-PSC-based asymmetric SC device. The device exhibits exceptionally superior electrochemical performance with a specific capacitance of 172 F g(-1) at 10 A g(-1) input current density and 97% capacity retention after 5000 cycles in a voltage window of 1.6 V. The results confirm the superiority of NCS STFA||SBN-PSC deviceas an excellent high-energy and high-power SC.
Keywords: Asymmetric supercapacitor device; NiCo2S4; pseudocapacitor; Surface charge storage

In situ solid-state synthesis of nitrogen-enriched porous carbon nanosheets from petroleum coke for lithium-ion hybrid capacitors - Benoy, Santhi Maria; Das, Anoushka K.; Sarmah, Debashis; Pawar, Meenakshi; Shelke, Manjusha V.; Saikia, Binoy K. (Energy & Fuels, 2025)
Lithium-ion capacitors (LICs) have emerged as a next-generation energy storage technology, offering a unique balance between the high energy density of lithium-ion batteries and the fast charge-discharge capability of supercapacitors. However, the development of high-performance anode materials remains a major challenge due to the trade-off between capacity, rate capability, and long-term cycling stability. Herein, we report a novel in situ solid-state synthesis approach for the scalable production of nitrogen-enriched porous carbon nanosheets (mBG1) from petroleum coke, an abundant industrial byproduct. The hierarchical porosity and optimized nitrogen functionalities of mBG1 facilitate rapid lithium-ion diffusion, enhanced electronic conductivity, and robust structural stability. Electrochemical characterization in lithium-ion half-cells demonstrates an exceptional specific capacity of 388 mAh g-1 at 0.1 A g-1, with an outstanding capacity retention of 92.7% over 1000 cycles (261.2 mAh g-1) at 1 A g-1. To validate its practical applicability, a full LIC coin cell was fabricated using mBG1 as the anode and commercial super activated carbon (super AC) as the cathode, achieving a specific capacitance of 44 F g-1 at 1 A g-1, a high energy density of 93.29 Wh kg-1 at 0.5 A g-1, and an impressive power density of 20.34 kW kg-1 at 10 A g-1, with 74% capacitance retention after 5000 cycles. The integration of ultrahigh nitrogen doping, hierarchical porosity, and scalable synthesis techniques offers a new pathway for designing next-generation lithium-ion capacitors with enhanced efficiency, stability, and economic viability. These findings establish mBG1 as a high-performance, scalable, and sustainable anode material for next-generation LICs, offering a transformative pathway for the valorization of petroleum coke in advanced energy storage applications.